Cortisol, cytokines, and hippocampal volume interactions in the elderly - Sudheimer, Keith D.; O'Hara, Ruth; Spiegel, David; Powers, Bevin; Kraemer, Helena C.; Neri, Eric; Weiner, Michael; Hardan, Antonio; Hallmayer, Joachim; Dhabhar, Firdaus S. (Frontiers in Aging Neuroscience, 2014)
Separate bodies of literature report that elevated pro-inflammatory cytokines and cortisol negatively affect hippocampal structure and cognitive functioning, particularly in older adults. Although interactions between cytokines and cortisol occur through a variety of known mechanisms, few studies consider how their interactions affect brain structure. In this preliminary study, we assess the impact of interactions between circulating levels of IL-1Beta, IL-6, IL-8, IL-10, IL-12, TNF-alpha, and waking cortisol on hippocampal volume. Twenty-eight community-dwelling older adults underwent blood draws for quantification of circulating cytokines and saliva collections to quantify the cortisol awakening response. Hippocampal volume measurements were made using structural magnetic resonance imaging. Elevated levels of waking cortisol in conjunction with higher concentrations of IL-6 and TNF-alpha were associated with smaller hippocampal volumes. In addition, independent of cortisol, higher levels of IL-1beta and TNF-alpha were also associated with smaller hippocampal volumes. These data provide preliminary evidence that higher cortisol, in conjunction with higher IL-6 and TNF-alpha, are associated with smaller hippocampal volume in older adults. We suggest that the dynamic balance between the hypothalamic-pituitary adrenal axis and inflammation processes may explain hippocampal volume reductions in older adults better than either set of measures do in isolation.